Oriented Growth of Neural Stem Cell–Derived Neurons Regulated by Magnetic Nanochains - Xia, Lin; Zhang, Chen; Su, Kaiming; Fan, Jiangang; Niu, Yuguang; Yu, Yafeng; Chai, Renjie (Frontiers in Bioengineering and Biotechnology, 2022)
Neural stem cell therapy has become a promising cure in the treatment of neurodegenerative disorders. Owing to the anisotropy of the nervous system, the newly derived neurons need not only the functional integrity but also the oriented growth to contact with the partner cells to establish functional connections. So the oriented growth of the newly derived neurons is a key factor in neural stem cell–based nerve regeneration. Nowadays, various biomaterials have been applied to assist in the oriented growth of neural stem cell–derived neurons. However, among these biomaterials, the magnetic materials applied in guiding the neuronal growth are still fewer than the other materials, such as the fibers. So in this work, we developed the magnetic nanochains to guide the oriented growth of neural stem cell–derived neurons. With the guidance of the magnetic nanochains, the seeded neural stem cells exhibited a good arrangement, and the neural stem cell–derived neurons showed well-oriented growth with the orientation of the nanochains. We anticipated that the magnetic nanochains would have huge potential in stem cell–based nerve regeneration.